Assessing the amount of Pseudomonas aeruginosa and the amount of Heavy metals, Lead (Pb) and Chromium (Cr) from household water from different industrial zones of Dhaka Division (Hazaribagh and Savar) - Uddin, Md Raihan; Ishrat, Sadia (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.